Canine Detection of the Volatile Organic Compounds Related to Cervical Cancer Cells - Rodríguez Esquivel, Miriam; Jimenez Vega, Florinda; Sánchez Pérez, José Alejandro; Guerrero-Flores, Héctor; Salcedo, Emanuel; Apresa García, Teresa; Valdivia Flores, Alejandra; Aldariz, Rodrígo; Salcedo, Mauricio (Intechopen, 2021)
The use of trained dogs for the detection of volatile biomarkers in biological samples has great potential to be used for non-invasive diagnosis and monitoring of several diseases such as cancer. It offers early, highly accurate detection with fast response times, non-invasive to patients and allows for repeated sampling. The aforementioned methods are useful as a portable technology to increase detection, screening, and monitoring coverage in populations at risk. In this sense, Cervical Cancer (CC) has become a public health concern of alarming proportions in many developing countries, particularly in low-income sectors and marginalized regions due to different factors that limit the coverage of screening methods and the acceptance rates of women attending their routine gynecological examination. As such, early detection is a crucial medical factor in improving not only their population’s quality of life but also its life expectancy. For the above, the great odor detection threshold exhibited by dogs is not unheard of and represents a potential opportunity to develop an affordable, accessible, and non-invasive method for detection of CC with high sensibility and specificity values.